Feeding Practice and Nutrition status of Under-five Year’s Children in Dalit Community in Darchula - Joshi , Ohmprakash; Bist , Suraj Kumar (Shiksha Shastra Saurabh, 2024)
This study aims to find out the feeding practices of under-five-year-old children, and to find out the relationship between socio-economic condition and nutritional status of less than five-year-old children in the study area. The study was conducted in Shailyshikhar Municipality-07 with the sample 98 mothers and 115 children as sample selected purposively using using census method. The study reveals that most of the mothers were found unaware of how to feed, what to feed and when to feed with the appropriate skill of preparing colostrum feeding, frequency of feeding and bottle feeding. The frequency of feeding babies and nutritional food practices were found poor. Furthermore, the study showed that 28.89 per cent of boys were not gaining proper weight for their age properly, 22.22 per cent were not gaining proper weight as per their height; 22.64 per cent of girls had low weight as per their and 33.96 per cent of girls had low weight as their age. This study found that there was no proper feeding practice for children under five years old due to the lack of knowledge awareness and of the occupational composition of mothers. The nutritional status of the children depends on various factors such as breastfeeding, colostrum feeding, and duration of appropriate feeding, knowledge of the mother, proper feeding economic and social status and so on.